Bond strength of composite-resin and resin-modified glass ionomer to bleached enamel: Delay bonding versus an antioxidant agent - Hamid Mazaheri; Maryam Khoroushi; Ehsan Shafiei; Reza Ghorbanipour; Fateme Majdzade (Wolters Kluwer Medknow Publications, 2011)
Objectives: As enamel bond strength of the resin-modified materials is reduced after bleaching, a delay bonding of at least 1 week is recommended. This study investigated the efficacy of 10% sodium ascorbate hydrogel on the bond strength of bleached enamel as an antioxidant agent. Materials and Methods: Ninety-six human, sound molars divided into eight groups. Buccal enamel surfaces of specimens in two negative control groups after preparation were bonded by the Z100 CR using the single-bond adhesive and Vitremer RmGI. Specimens in other groups after enamel preparation were bleached with 9.5% hydrogen peroxide. In two positive control groups, bonding of CR and RmGI was performed immediately after bleaching. Specimens in two other groups were immersed in distilled water after bleaching, and then CR and RmGI were bonded after 1 week. In last two groups, 10% sodium ascorbate hydrogel was applied after bleaching, and then they were bonded by CR and RmGI. The specimens were placed under shear force. Statistics: ANOVA and Duncan's multiple range tests were used for data analysis. Results: Application of 10% sodium ascorbate hydrogel immediately before bonding and delay bonding for 1 week eliminated the negative effects of bleaching on CR and RmGI enamel bond strength. Conclusion: Application of 10% sodium ascorbate hydrogel or 1 week period elapsed after bleaching could significantly increase the enamel bond strength to a normal value.